2019
DOI: 10.21467/ajss.5.1.81-92
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Seasonal Migration of Rural Livelihood: Capital Formation Perspective

Abstract: Globally, farming communities migrates considering it as a livelihood strategy, especially given unprecedented environmental change. Because migration facilitates poverty reduction, education improvement, entrepreneurial investments and even the economic evolution of the origin areas. Farmers in the northern region of Bangladesh migrate during the slack season when farming activities are not up to the mark. Driven by this context, this study examined the principal actors, the pattern of seasonal migration in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Studies of Deshingkar and Daniel (2003), Islam et al (2019), Keshri and Bhagat (2010), Khatun and Roy (2016), Rafique (2003), Rai (2020), Rogaly and Coppard (2003) and Rogaly et al (2001) have shown the importance of seasonal migration in livelihood strategies of the SEBLP in rural areas and has been increasingly becoming an accumulative alternative for them. Numerous studies (Debnath, 2020;Garikipati, 2008;Ghosh and Mal, 2017;Keshri and Bhagat, 2010;Keshri and Bhagat, 2012;Rademacher-Schulz et al, 2014;Rafique, 2003;Rogaly and Coppard, 2003;Rogaly et al, 2001) have pointed out several factors of seasonal migration, where job opportunities and poverty are the primary reasons behind seasonal migration.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of Deshingkar and Daniel (2003), Islam et al (2019), Keshri and Bhagat (2010), Khatun and Roy (2016), Rafique (2003), Rai (2020), Rogaly and Coppard (2003) and Rogaly et al (2001) have shown the importance of seasonal migration in livelihood strategies of the SEBLP in rural areas and has been increasingly becoming an accumulative alternative for them. Numerous studies (Debnath, 2020;Garikipati, 2008;Ghosh and Mal, 2017;Keshri and Bhagat, 2010;Keshri and Bhagat, 2012;Rademacher-Schulz et al, 2014;Rafique, 2003;Rogaly and Coppard, 2003;Rogaly et al, 2001) have pointed out several factors of seasonal migration, where job opportunities and poverty are the primary reasons behind seasonal migration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Temporary or seasonal migration is a short-term, repetitive or circular migration with a motive of a temporary change of residence (Zelinsky, 1971). Socioeconomically backward and landless people (SEBLP) of the rural area seasonally migrate to the nearest prosperous region because of unbalanced economic growth (Berchoux et al, 2019;Debnath, 2020;Debnath and Nayak, 2020;Islam et al, 2019;Keshri and Bhagat, 2010) and absence of duty in the family farm (Lindstrom and Ramirez, 2010;Mishra, 2020). It is very popular, especially in the slack season of agriculture to cope up with the poverty and unemployment (Debnath and Nayak, 2020;Ellis, 2008;Gill, 2003;Mishra, 2016;Serrat, 2017).…”
Section: Introductionmentioning
confidence: 99%